Analisis Soal Evaluasi Sumatif Matematika Kelas 8 Tipe HOTS di MTs Yanuri Annamira Untuk Mendukung Literasi Matematika Melalui Komunikasi Efektif - Rismayanti, Rena; Fauziah, Reifa Aulia Nur; Mudjenan, Ikhsan Muhamad; Utami, Haliza Widiya; Fahira, Hana; Setiawan, Budi (CV. ITTC INDONESIA, 2024)
Abstract Strong mathematical literacy is an important provision for students in facing challenges in the modern era filled with ever-growing information and knowledge. The research we are reviewing aims to evaluate the extent to which summative evaluation questions for grade 8 mathematics at MTs Yanuri Annamira meet the Higher Order Thinking Skills (HOTS) standards in supporting the development of students' mathematical literacy through effective communication between teachers and students. This study uses a qualitative approach with a descriptive method to analyze the characteristics of the questions through document analysis and interviews with related mathematics teachers. The results of the study revealed that of the 35 questions analyzed, 48% were classified as HOTS questions that were able to stimulate students' critical and analytical thinking skills. However, the majority of the questions were still at the intermediate cognitive level (PISA levels 1 to 4), with a minimum of questions that encouraged reflective thinking and complex problem solving (levels 5 and 6). These findings indicate the importance of the role of effective communication between teachers and students in the learning process. Teachers need to convey HOTS questions in a clear, focused, and appropriate manner to students' needs, and establish open communication so that students feel comfortable expressing the difficulties or obstacles they face. Through good communication, teachers can adjust the quality and difficulty level of questions according to students' needs, so that the proportion of higher HOTS questions (C4 and above) can increase. This study recommends strengthening teacher-student interactions to create a learning environment that supports the development of mathematical literacy and high-level thinking skills to face global challenges. Keywords: Higher Order Thinking Skills (HOTS), Mathematical Literacy, PISA Levels, Summative Mathematics Evaluation, 21st Century Education Abstract Literasi matematika yang kuat menjadi bekal penting bagi peserta didik dalam menghadapi tantangan di era modern yang dipenuhi oleh informasi dan pengetahuan yang terus berkembang. Penelitian yang kita kaji ini bertujuan untuk mengevaluasi sejauh mana soal evaluasi sumatif matematika kelas 8 di MTs Yanuri Annamira memenuhi standar Higher Order Thinking Skills (HOTS) dalam mendukung pengembangan literasi matematika peserta didik melalui komunikasi efektif antara guru dan siswa. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif untuk menganalisis karakteristik soal melalui analisis dokumen dan wawancara dengan guru matematika terkait. Hasil penelitian mengungkapkan bahwa dari 35 soal yang dianalisis, 48% tergolong soal HOTS yang mampu merangsang kemampuan berpikir kritis dan analitis siswa. Namun, mayoritas soal masih berada pada level kognitif menengah (PISA level 1 hingga 4), dengan minimnya soal yang mendorong pemikiran reflektif dan pemecahan masalah kompleks (level 5 dan 6). Temuan ini menunjukkan pentingnya peran komunikasi yang efektif antara guru dan siswa dalam proses pembelajaran. Guru perlu menyampaikan soal HOTS dengan cara yang jelas, terarah, dan sesuai kebutuhan peserta didik, serta menjalin komunikasi terbuka agar siswa merasa nyaman mengemukakan kesulitan atau kendala yang dihadapi. Melalui komunikasi yang baik, guru dapat menyesuaikan kualitas dan tingkat kesulitan soal sesuai kebutuhan siswa, sehingga proporsi soal HOTS yang lebih tinggi (C4 ke atas) dapat meningkat. Penelitian ini merekomendasikan penguatan interaksi guru-siswa untuk menciptakan lingkungan belajar yang mendukung pengembangan literasi matematika dan kemampuan berpikir tingkat tinggi guna menghadapi tantangan global. Kata Kunci: Evaluasi Sumatif Matematika, Higher Order Thinking Skills (HOTS), Literasi Matematika, Pendidikan Abad 21, PISA Level